Clinico-hematological profile of anaemia in adolescent girls in a tertiary care hospital of North India - Sharma, Manoj Kumar; Parashar, Preeti; Jain, Neelima (International Journal of Advances in Medicine, 2019)
Background: Anaemia in adolescent girls leads to foetal morbidity and mortality in future. The current study was done with the aim to study the clinico-haematological profile of anaemia in adolescent girls in a tertiary care hospital of North India. Methods: An observational study was conducted among 50 adolescent girls with anaemia (Hb <12 g/dl) in the Department of Medicine in collaboration with Department of Pediatrics and Department of Haematology at VMMC and Safdar-jang Hospital, New Delhi. Detailed previous history of the patients was collected. Blood samples were collected from all the patients and analysed for hematological parameters. Data were analysed statistically and p values less than 0.05 was considered significant. Results: The prevalence of anaemia was common in the patients of age group of 15-19 years (58%). The common symp-tom observed was fatigue (82%). Pallor was the common sign noticed in 66% patients. Majority of the patients with anaemia belongs to upper lower class (52%). Mean value of haemoglobin was high (7.80±1.22) in microcytic hypo-chromic anaemia compared to other types of anaemia. Serum iron levels were low in both microcytic and dimor-phic group but the difference was statistically not significant (p=0.43). Serum vitamin B12 levels were low in mac-rocytic and dimorphic anaemia and the difference was statistically significant (p=0.001). Conclusions: This study showed that nutritional deficiency anaemia was more prevalent in adolescent girls of age group between 15-19 years of upper lower socioeconomic status. Nonspecific symptoms like fatigue and weakness should not be ignored in the adolescent girls as they could be important indicators towards incidence of anaemia in these patients.